GARAP GENDING ALIH PATHET DALAM LARAS SLÈNDRO GAYA SURAKARTA - Harun Isma'il; Bambang Sunarto (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2022)
This paper contains an explanation of the garap gending alih pathêt. The problems revealed are related to changes of the system garap gending and considerations for doing of alih pathêt. The two problems are studied using the concept of garap and supported by other concepts including: balungan, sèlèh, and phrase. The garap alih pathêt is focused in the gending-gending laras slèndro. The gending used as the analysis material was selected based on the phenomenon of presentation carried out by pêngrawit. This study uses a qualitative research method with a descriptive analysis approach. The results showed that there were several categories of changes system garap gending in the laras sléndro. First, the change of the system garap gending by raising or lowering (N/T) one note bar in the case of Sinom Parijatha pathêt manyurå to pathêt sångå. Second, the change of the system garap gending by raising or lowering (N/T) two tone bars in the case of the Mugirahayu pathêt manyurå to Grompol pathêt nêm. One element of consideration for garap gending alih pathêt is the similarity of the contours of the balungan melody. Garap gending alih pathêt cannot occur when the contour elements of the balungan melody are not the same.